Dissemination of resistance plasmids among gentamicin-resistant enterobacteria from hospital patients. Issue 6294 (19th September 1981) - Knight, S; Casewell, M
Abstract : Out of 184 patients who were infected or colonised with gentamicin-resistant enterobacteria, 17 (9%) harboured more than one strain. Single antibiotic-resistance plasmids were common to more than one of the different organisms isolated from nine patients, strongly suggestive of in-vivo conjugation. An "epidemic" plasmid with a molecular weight of approximately 110 megadaltons was found in 11 distinct strains isolated from four patients. Seven of the organisms harbouring this plasmid were Klebsiella aerogenes. Spread of multiple-resistance plasmids among endemic gentamicin-resistant enterobacteria is not uncommon, and these organisms provide a reservoir of plasmids that may ultimately spread to more pathogenic genera.